Isolation of phages active against Pseudomonas aeruginosa and Staphylococcus epidermidis from human breast milk, an underexplored microbiome - Dr Steven De Soir; Dr. Jeroen Waegemans; Professor Rob Lavigne; Dr. Jean-Paul Pirnay; Dr. Maya Merabishvilli; Professor Jeremy Barr; Professor Françoise Van Bambeke; Dr. Daniel De Vos (International Journal of Infectious Diseases)
Introduction: Human Breast milk (HBM) is a rich nutrient source as well as a protective agent for the baby. It seems also to be a primary gut inoculator and immune booster. The HBM microbiome is still underexplored while the entero-mammary pathway, including the microbial transfers from the mothers’ gut into the HBM, is not yet well understood. Although several research groups already showed the presence of phages as well as bacteria, mainly through metagenomic approaches, the isolation of phages and their target bacterial hosts is not yet well described while the implications for the baby are of huge importance for the development of a healthy gut microbiome. Methods: HBM samples were collected at multiple timepoints from one healthy individual. Subsequent centrifugation and filtration followed by an enrichment protocol allowed for the isolation of bacteriophages. Phage characterization was performed with genetic sequencing, host range evaluations along with metabolic assays (Omnilog Biotyper) delineating possible therapeutic potential of the isolated phages. Results & Discussion: In the present work, 6 bacteriophage clones (ADSPa1-6) active against P. aeruginosa and one bacteriophage targeting S. epidermidis (ADSSe) along with a bacterial target strain were de novo isolated from multiple HBM samples. Activity tests on a wide variety of target bacteria showed high therapeutic potential with lytic activity against all but one bacterial strain, while the isolation of a bacterial host strain implies a co-evolutionary aspect. Genetic sequencing additionally revealed a putative depolymerase gene within the genome of phage ADSSe. Conclusion: The HBM study results argue for the existence of a multi-functional entero-mammary pathway with a protective role for the baby beside its nutritional and immunological functions. This preliminary work further establishes the potential role bacteriophages may play in constituting and equilibrating the newly forming gut microbiome but demand further in-depth research into the HBM microbiome.